Co-stimulatory molecules in and beyond co-stimulation – tipping the balance in atherosclerosis? - Gerdes, Norbert; Zirlik, Andreas (Thrombosis and Haemostasis, 2011)
A plethora of basic laboratory and clinical studies has uncovered the chronic inflammatory nature of atherosclerosis. The adaptive immune system with its front-runner, the T cell, drives the atherogenic process at all stages. T cell function is dependent on and controlled by a variety of either co-stimulatory or co-inhibitory signals. In addition, many of these proteins enfold T cell-independent pro-atherogenic functions on a variety of cell types. Accordingly they represent potential targets for immune- modulatory and/or anti-inflammatory therapy of atherosclerosis. This review focuses on the diverse role of co-stimulatory molecules of the B7 and tumour necrosis factor (TNF)-superfamily and their downstream signalling effectors in atherosclerosis. In particular, the contribution of CD28/CD80/CD86/CTLA4, ICOS/ICOSL, PD-1/PDL-1/2, TRAF, CD40/CD154, OX40/OX40L, CD137/CD137L, CD70/CD27, GITR/GITRL, and LIGHT to arterial disease is reviewed. Finally, the potential for a therapeutic exploitation of these molecules in the treatment of atherosclerosis is discussed.
Keywords: Animal models; atherosclerosis; leukocyte function / activation; inflammatory mediators; immunity